Analisis Pengelolaan Lingkungan Belajar di RA Husna Al Fauzan Binjai - Zahida Azzahra; Perdina Rantika Nasution; Arie Dwi Ningsih (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyze the management of the learning environment at RA Husna Al Fauzan Binjai in creating a conducive learning space for early childhood development. The method used is descriptive qualitative with techniques including observation, interviews, and documentation. The results indicate that the management of the learning environment at RA Husna Al Fauzan adheres to early childhood education (ECE) pedagogical principles, encompassing physical space arrangement, the availability of educational play equipment, and the establishment of a supportive social climate. However, several challenges were identified, such as limited space and resources, which need to be addressed through parent collaboration and enhanced teacher capacity. This study recommends the need for a more systematic and sustainable management strategy to create a holistic learning environment.